Factors Affecting Construction Project Performance: Bharatpur Metro Case Study - Bagale, Shashi; Bohara, Niraj (Journal of UTEC Engineering Management, 2024)
DOI: https://doi.org/10.36344/utecem.2024.v02i01.002This study is conducted to evaluate the time, cost overrun, time-cost relationship and to identify and evaluate the major factors affecting the performance of construction projects in Bharatpur metropolitan city. The study of 11 recently completed ward office building construction projects, revealed that all of them experienced time overruns, ranging from 28% to 150% beyond the contract time. Additionally, 9 of the 11 projects suffered from cost overruns, ranging from 18.54% to 41.03% over the contract amount. In Bharatpur metropolitan city, there is a positive but moderately predictive relationship between construction time and project cost, with longer construction durations typically associated with higher project costs. A questionnaire survey involving 61 identified factors categorised into 9 groups was conducted, validated through the Content Validity test, Criterion Validity test and Cronbach’s Alpha tests. Analysis using Relative Importance Index (RII) determined that the most significant factors, agreed upon by all stakeholders, included project manager leadership skills, materials price escalation, average delay because of closure and materials shortage, design and drawing changes, subcontractor control, organisation liquidity and delayed payments of Relative Importance Index (RII) ranging from 0.513 to 0.925. The Spearman rank correlation (⍴), there is a significant agreement between the ranking of Client, consultant and contractor.